Rice Trade Trend And Policy Implication In Nepal (Agronomy Journal of Nepal, 2021)
This paper examines how rice external trade behaves over the recent six decades including major trading partners in the context of Nepal. Bringing the time series trade data from reliable sources, this study also attempts to highlight import dependency ratio, correlation of population and GDP per capita growth with total import and pin down plausible reasons behind these pictures. The correlation study between import data to population growth and GDP per capita showed a positive correlation with r values 0.71 (p